Math, asked by eshwaverma, 5 months ago

if x^2+1/x^2=6,find the value of x^4+1/x^4​

Answers

Answered by Aryan0123
5

Given :-

  • x² + 1/x² = 6

\\ \\

To find :-

♦ x⁴ + 1/x⁴ = ?

\\ \\

Solution :-

\\

 \bf{ {x}^{2}  +  \dfrac{1}{ {x}^{2} }  = 6} \\ \\

Squaring on both sides,

 \Rightarrow \sf{ \bigg( {x}^{2} +  \dfrac{1}{ {x}^{2} }  \bigg)  {}^{2}  =  {6}^{2}   } \\ \\

Split using (a + b)² = a² + b² + 2ab

 \Rightarrow \:  \sf{ ({x}^{2}) {}^{2} +     \bigg(\dfrac{1}{ {x}^{2} } \bigg) {}^{2}  +  \bigg(2. x . \dfrac{1}{x} \bigg) = 36 } \\

 \Rightarrow \:  \sf{x {}^{4}  +  \dfrac{1}{ {x}^{4} } + 2 = 36 } \\

 \Rightarrow \:  \sf{ {x}^{4}  +  \dfrac{1}{ {x}^{4} }  = 36 - 2} \\

 \therefore \:  \boxed{  \red{ \sf{{x}^{4}  +  \dfrac{1}{ {x}^{4} }  = 34}}}

Know more:

\boxed{\begin{minipage}{7 cm}\boxed{\bigstar\:\:\textbf{\textsf{Algebric\:Identity}}\:\bigstar}\\\\1)\bf\:(A+B)^{2} = A^{2} + 2AB + B^{2}\\\\2)\sf\: (A-B)^{2} = A^{2} - 2AB + B^{2}\\\\3)\bf\: A^{2} - B^{2} = (A+B)(A-B)\\\\4)\sf\: (A+B)^{2} = (A-B)^{2} + 4AB\\\\5)\bf\: (A-B)^{2} = (A+B)^{2} - 4AB\\\\6)\sf\: (A+B)^{3} = A^{3} + 3AB(A+B) + B^{3}\\\\7)\bf\:(A-B)^{3} = A^{3} - 3AB(A-B) + B^{3}\\\\8)\sf\: A^{3} + B^{3} = (A+B)(A^{2} - AB + B^{2})\\\\\end{minipage}}

Similar questions